Pengaruh Bimbingan Orang Tua melalui Aktivitas Belajar dan Motivasi terhadap Hasil Belajar Siswa - Sampurna, Rani Budiwati; Muncarno, Muncarno; Perdana, Ryzal (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The problem in this research was the low mathematics learning outcomes of grade V SD Kecamatan Labuhan Ratu. This research aimed to 1) analyze the effect of parental guidance on students mathematics learning outcomes, 2) analyze the effect of learning motivation on students mathematics learning outcomes, and 3) analyze the effect of parental guidance and learning motivation on students mathematics learning outcomes. The data in this research was analy by using quantitative research. This type of this research was ex post facto. The population of this research was 502 students and the total sample was 84 students which waswereken from SD Negeri 2 Labuhan Ratu dan SD Negeri 2 Sepang Jaya. The sampling technique in this research was cluster sampling which was part of the probability sampling technique. Questionnaire and documentation were used as data colletechniqueshnique. Data analysis used a simple linear regression and multiple linear regression formulas. The results showed that there was a significant effect between parental guidance to learn mathematics which was indicated by tFountunt ≥ Ftable (4,55 ≥ 3,95); there was a significant effect between motivation to learn mathematics which was indicated by the Fcount ≥ Ftable (5,90 ≥ 3,95); there was a significant effect between parental guidance and motivation to learn mathematics in grade V SD Kecamatan Labuhan Ratu, which was indicated by the Fcount ≥ Ftable (4.04≥ 3.10).